2014
DOI: 10.1177/0194599814541627a34
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Late Tracheostomy: A Systematic Review and Meta‐analysis

Abstract: Oral PresentationsP39 devised in conjunction with emergency medicine that minimizes the duration of nasal packing and length of hospitalization and reduces the total cost of care. Implementation of the pathway required changes in the electronic medical record and educational programs.Conclusions: Implementation of a CCP requires evaluation of current practices and the standard of care followed by input from institutional decision makers. Quantifying improvement requires retrospective normative data with ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 0 publications
2
61
0
3
Order By: Relevance
“…In the present study, the duration of ICU stay was found significantly shorter in patients diagnosed with COPD than in those not diagnosed. We believe that detailed Prolonged intubation and ICU stay increase not only hospital costs but also mortality and morbidity rates (12)(13)(14). In our study, a significant negative correlation was also found between FEV1 and duration of intubation in patients who underwent mitral valve surgery.…”
Section: Discussionsupporting
confidence: 54%
“…In the present study, the duration of ICU stay was found significantly shorter in patients diagnosed with COPD than in those not diagnosed. We believe that detailed Prolonged intubation and ICU stay increase not only hospital costs but also mortality and morbidity rates (12)(13)(14). In our study, a significant negative correlation was also found between FEV1 and duration of intubation in patients who underwent mitral valve surgery.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, outcomes measured at the time of hospital discharge may inadequately capture patient-centered outcomes as multiple significant events in the care of patients with tracheostomy occur post-discharge 7 . Furthermore, several trials and meta-analyses related to tracheostomy timing 14,17,19,50 were published after 2012 and could have affected tracheostomy timing practice-patterns after our study period; changes in practice patterns after 2012 require further study. Additionally, conditions suspected at the time of admission which could have affected decisions regarding tracheostomy timing but were ultimately not confirmed, such as suspected cervical spine injury, could not be captured by the NIS.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we investigated the association between early tracheostomy rates and total tracheostomy utilization rates within hospitals, and explored patient outcomes associated with early tracheostomy. Some have theorized 1719 that a heterogeneous case-mix of patients included in studies of tracheostomy timing 11,20–28 may obscure potential benefits of early tracheostomy; therefore, we evaluated utilization and outcomes separately among patients with the two most common indications for tracheostomy – trauma and pneumonia/sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta‐analysis performed by Liu et al investigating the effects of early tracheostomy found a reduction in ICU LOS (−9.13 days, 95% CI: −17.55 to −0.70 days) . Among the included studies, early and late tracheostomy varied between 2 and 8 days, and 6 and 28 days, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%